2013
DOI: 10.1098/rspb.2013.0273
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome diversity and population structure of the giant squid Architeuthis : genetics sheds new light on one of the most enigmatic marine species

Abstract: Rua do Porto 18, 9939 430 Sao Joao, Lajes do Pico, Açores, PortugalDespite its charismatic appeal to both scientists and the general public, remarkably little is known about the giant squid Architeuthis, one of the largest of the invertebrates. Although specimens of Architeuthis are becoming more readily available owing to the advancement of deep-sea fishing techniques, considerable controversy exists with regard to topics as varied as their taxonomy, biology and even behaviour. In this study, we have characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 56 publications
4
48
0
1
Order By: Relevance
“…There are both fish and squid species that exhibit similar levels of connectivity across comparable spatial scales (e.g., orange roughy (Hoplostethus atlanticus), Varela et al, 2012; giant squid (Architeuthis spp. ), Winkelmann et al, 2013) and it is likely that there are aspects of these species' population biology that are common. Thompson et al (2013) suggests that, given stranding patterns, seasonal shifts in distribution associated with the calving season are likely in Gray's beaked whales, perhaps in relation to a dependency on inshore waters.…”
Section: Discussionmentioning
confidence: 99%
“…There are both fish and squid species that exhibit similar levels of connectivity across comparable spatial scales (e.g., orange roughy (Hoplostethus atlanticus), Varela et al, 2012; giant squid (Architeuthis spp. ), Winkelmann et al, 2013) and it is likely that there are aspects of these species' population biology that are common. Thompson et al (2013) suggests that, given stranding patterns, seasonal shifts in distribution associated with the calving season are likely in Gray's beaked whales, perhaps in relation to a dependency on inshore waters.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic study on whole mitochondrial DNA of the giant squid (Winkelmann et al 2013) demonstrated that there was no detectable phylogenetic structure at the mitochondrial level among 43 samples obtained from oceans all over the world, and the level of nucleotide diversity was exceptionally low. These results strongly support the hypothesis that only one global species, A. dux, is valid.…”
Section: Communicated By M Vecchionementioning
confidence: 99%
“…Altmetrics are best used to gauge immediate interest and attention towards recently published work and to identify channels and geographical locations where mentions and reference occur. Thus, the recently published article Mitochondrial genome diversity and population structure of the giant squid Architeuthis: Genetics sheds new light on one of the most enigmatic marine species, which is available in bibliography-only format in the repository [42], has already generated remarkable attention across social and researcher-oriented platforms including science blogs, Facebook and Twitter (Figure 8). However, it will be advisable to wait at least a couple of years before confirming whether such interest in the short-run will have any influence on citation counts.…”
Section: More Players Gathering Scholarly Citations and Referencesmentioning
confidence: 99%